Does income inequality have lasting effects on health and trust?. (January 2016) - Rözer, Jesper Jelle; Volker, Beate
Abstract: According to the income inequality hypothesis, income inequality is associated with poorer health. One important proposed mechanism for this effect is reduced trust. In this study, we argue that income inequality during a person's formative years (i.e., around age 16) may have lasting consequences for trust and health. Multilevel analyses of data from the combined World Values Survey and European Values Study that were collected between 1981 and 2014 support our prediction and show that income inequality is associated with ill health in young adults, in part because it reduces their social trust. The negative consequences of income inequality remain stable for a substantial period of life but eventually fade away and have no effect after age 36. Highlights: Income inequality is associated with poorer adolescent health. Income inequality affects young adults in part because it reduces social trust. Negative consequences of income inequality on health fade away after approximately age 36.